Pengaruh Harga, Online Customer Rating, Dan Sistem Pembayaran Cash On Delivery Terhadap Keputusan Pembelian Di E-Commerce TikTok Shop (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2019) - Achmad Naufal Miqdad; Budi Wahono; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Purposive sampling of 2019 batch students of economics and business at Islamic University of Malang served as the case study for this study, which sought to determine and analyze the effect of price, online customer rating, and the cash on delivery payment system on customer purchasing decisions in the e-commerce TikTok shop. The maholtra formula was also used to count the samples. 75 respondents were used as samples in this study. The information examination strategies utilized in this exploration are legitimacy and unwavering quality tests, normality tests, multicollinearity tests and heteroscedasticity tests, different straight relapse examination, speculation testing, and coefficient of assurance test (Changed r2). Using SPSS to analyze the process. According to the study's findings, customer purchasing decisions are influenced by price, online customer rating, and cash on delivery payment systems simultaneously. Prices do not significantly influence customer purchasing decisions, but online customer rating and systems that accept cash on delivery. Keywords: Price, Online Customer Rating, Cash On Delivery Payment Systems, Purchase Decision.